Peran Majelis Taklim Babakan Jamanis dalam Meningkatkan Sikap Moderasi Beragama di Desa Karangbenda, Kecamatan Parigi, Kabupaten Pangandaran: Pengabdian - Haryono, Pauzan; Khoir HS, Abdul; Gunawan, Syahrul; Sahidin; Ubaidillah; Kholilah, Aulia; Maryani; Syarif, Aiman; Ibnu Nurrahman, Pandu; Nubzatussaniyyah, Nunu; Roihan Ramadhan, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Majelis taklim, as a non-formal religious education institution, plays a strategic role in promoting religious moderation, particularly in addressing grassroots intolerance and radicalism. This community engagement program aimed to strengthen the role of Majelis Taklim Babakan Jamanis, Karangbenda Village, Pangandaran, in fostering religious moderation through educational and participatory approaches. Activities included training, discussions, and mentoring involving congregation members, religious leaders, and local authorities, focusing on values such as tawassuth, tasamuh, i’tidal, and musawah. As a result, the majelis taklim fulfilled five strategic functions: inclusive religious education, peaceful and contextual preaching, social solidarity, partnership in public education, and an open space for interfaith dialogue. This program contributed to contextualizing and sustaining religious moderation, highlighting the potential of empowering local religious institutions to build a tolerant and peaceful religious ecosystem.